The Correlation Between Career Planning, Attribution and Students Learning Motivation - Rendi Samosir; Herman Nirwana; Alizamar Alizamar (Global Econedu, 2020)
Learning motivation has an important role in student learning process. The objectives of this research are to describe students career planning, to describe student attribution, to describe students learning motivation, to examine the correlation between career planning and students learning motivation, to examine the correlation between attribution and students learning motivation, and to examine the correlation between career planning and students learning motivation. The research uses correlational descriptive type of quantitative method. The population of research are 435 students of Curriculum and Education Technology Major in State University of Padang. A sample of 208 students was chosen by proportional random sampling technique. The instruments used were career planning, attribution, and students learning motivation. Data were analyzed by descriptive statistics, linear regression and multiple regression. The research findings show that 1) in general students already have a good career planning 2) student attribution is in the middle category 3) student learning motivation is in high category 4) there is a positive significant correlation between career planning and student learning motivation 5) there is a positive significant correlation between attribution and learning motivation 6) there is a positive significant correlation between career planning and attribution with student learning motivation, and (7) the implication of this research findings can be used as a feedback for making a program of guidance and counseling service which can improve career planning, attribution, and students learning motivation.